Mammography in asymptomatic women aged 40-49 years - Silva, Flávio Xavier; Katz, Leila; Souza, Alex Sandro Rolland; Amorim, Melania Maria Ramos (Revista de Saúde Pública, 2014)
OBJECTIVE To assess findings of mammography of and interventions resulting from breast cancer screening in women aged 40-49 years with no increased risk (typical risk) of breast cancer. METHODS This cross-sectional study evaluated women aged 40-49 years who underwent mammography screening in a mastology reference center in Recife, PE, Northeastern Brazil, between January 2010 and October 2011. Women with breast-related complaints, positive findings in the physical examination, or high risk of breast cancer were excluded. RESULTS The 1,000 mammograms performed were classified into the following Breast Imaging-Reporting and Data System (BI-RADS) categories BI-RADS 0, 232; BI-RADS 1, 294; BI-RADS 2, 294; BI-RADS 3, 16; BI-RADS 4A, 2; BI-RADS 5, 1. There was one case of grade II invasive ductal carcinoma and various interventions, including 469 ultrasound scans, 53 referrals to mastologists, 11 cytological examinations, and 8 biopsies. CONCLUSIONS Mammography screening in women aged 40-49 years with typical risk of breast cancer led to the performance of other interventions. However, it also resulted in increased costs without demonstrable efficacy in decreasing mortality.